Altmetric and bibliometric analysis of influential articles in reproductive biology, 1980–2019. Issue 2 (August 2022) - Park, Selena; Blackledge, Kristin; Ananth, Cande; Sauer, Mark; Brandt, Justin
Abstract: Research question: What are the most influential articles in reproductive biology journals from 1980 to 2019 according to Altmetric Attention Score (AAS), number of citations and Relative Citation Ratio (RCR)? Design: Cross-sectional study of reproductive biology articles indexed in the National Institutes of Health Open Citation Collection from 1980 to 2019. Data were downloaded on 20 May 2021. The 100 articles with highest AAS, RCR and number of citations were analysed. Results: Twenty-one reproductive biology journals were identified, including 120, 069 articles published from 1980 to 2019. In total 227 reproductive biology classics were identified due to some overlap between the three lists. Compared with the 100 articles with the highest AAS (after excluding articles featured on both lists), the 100 top-cited articles were older (2014 versus 2001, mean difference [95% confidence interval] 13.5 [11.5, 15.5]), less likely to be open access (64% versus 85%), more likely to be reviews (42% versus 12%) and less likely to be observational studies (9% versus 51%) and randomized clinical trials (0% versus 5%). These same trends were observed in analyses comparing the 100 articles with highest AAS to the 100 articles with highest RCR. The most common topic was assisted reproduction, but prominent topics included infertility for top AAS articles, reproductive technology in animals for top-cited articles, and polycystic ovary syndrome for top RCR articles. Conclusions: Formerly, influential articles in reproductive biology journals were evaluated by absolute citation rates and subject to limitations of conventional bibliometric analysis. This is the first comprehensive study to use altmetrics and citation-based metrics to identify reproductive biology classics.